2022
DOI: 10.3390/molecules27020408
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Petal Structure and Fragrance Components of the Nymphaea hybrid, a Precious Water Lily

Abstract: Nymphaea hybrid, a precious water lily, is a widely-cultivated aquatic flower with high ornamental, economic, medicinal, and ecological value; it blooms recurrently and emits a strong fragrance. In the present study, in order to understand the volatile components of N. hybrid and its relationship with petals structure characteristics, the morphologies and anatomical structures of the flower petals of N. hybrid were investigated, and volatile compounds emitted from the petals were identified. Scanning and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…They are mainly used as a scent and there is no sufficient evidence that they act as antibacterial drugs intended for combating the oral microbiota (or even as preservatives), but there are such possibilities. Benzyl alcohol is mainly used as a fragrance and preservative [ 114 , 115 ] and only its derivative (2,4-dichlorobenzyl alcohol) is used as a mild oral and pharyngeal antiseptic. Limonene [ 99 , 116 , 117 ], linalool [ 99 , 117 ], citral [ 118 ] and cinnamal (cinnamaldehyde) [ 119 ] exhibit a non-negligible activity against oral pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…They are mainly used as a scent and there is no sufficient evidence that they act as antibacterial drugs intended for combating the oral microbiota (or even as preservatives), but there are such possibilities. Benzyl alcohol is mainly used as a fragrance and preservative [ 114 , 115 ] and only its derivative (2,4-dichlorobenzyl alcohol) is used as a mild oral and pharyngeal antiseptic. Limonene [ 99 , 116 , 117 ], linalool [ 99 , 117 ], citral [ 118 ] and cinnamal (cinnamaldehyde) [ 119 ] exhibit a non-negligible activity against oral pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocallis (Nymphaeaceae), with the exception of N. rudgeana, in which the emission of (methoxymethyl)benzene was dramatically reduced during the staminate phase, and floral scent discharge was greater in the pistillate phase than in the staminate phase [30]. Zhou et al [33] analyzed the chemical compositions of four kinds of N. hybrid, and found that the major volatile components were benzyl alcohol, pentadecane, trans-α-bergamotene, (E)-β-farnesene, and (E6,E9)-heptadecadiene, which released the sweeter fruity floral scent. Previous studies found that the main VOCs in tropical water lilies were benzyl alcohol, benzyl acetate, 6(E),8(E)-heptadecadiene, 6,9-heptadecadiene, pentadecane, 8-heptadecene, transβ-farnesene, and Z,Z-10,12-hexadecadienal, while pentadecane, undecane, cis-ocimene, tridecane, 8-heptadecene, 6,9-heptadecadiene, and tetradecane were the major VOCs in hardy water lilies [32,42].…”
Section: Differences In Floral Components Of N 'Eldorado' At Differen...mentioning
confidence: 99%
“…Su et al [32] studied the volatile components of the flowers of 62 water lily varieties; a total of 72 volatile components were detected with alkenes being most common. Zhou et al [33] found that alkenes, alcohols, and alkanes were abundant in the flower petals of N. hybrid, and the difference in volatile compounds in different N. hybrids was closely related to the structure of the perianth.…”
Section: Introductionmentioning
confidence: 99%
“…Nymphaea hybrid (NH), a water lily that belongs to the Nymphaeaceae family, is known as the "Nine Ranks Perfume Lotus" for its nine colors after being cultivated in China in the 1970s [1][2][3]. The reason why its flowers have many colors is that the petals precisely contain a lot of anthocyanins and flavonoids [3]. In addition, NH flowers also have polysaccharide crude fiber, protein and other components.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, the alcohol extracts (mainly flavonoids and polyphenols) from NH have been proven to have antioxidant activity, including strong scavenging activities on free radical and lipid peroxidation inhibition ability, indicating to some extent that the alcohol extract from NH can act as anti-aging active material in the field of cosmetics [4,5]. Moreover, various extracts of NH are also used in various fields such as food [3,6] and medicine [4,7]. However, most of the research on NH has been focused on alcohol extracts, which often face solubility, stability and other problems for application in the aqueous systems.…”
Section: Introductionmentioning
confidence: 99%